INFORMATION AND ANALYTICAL SYSTEMS FOR PROCESSING BIG DATA (BIG DATA) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article is for those who are interested in big data and will be primarily useful for those who collect, analyze and use it. Big data will only grow with the use of computers in work activities, and there will be a need for efficient processing, storage and analysis of this data. There is a need to use these data in forecasting and planning with the development of information technology. Since data analytics can give a more accurate analysis, and, accordingly, a more accurate result of the analysis can help make the right decision. The significance of big data begins to appear only at the stage of their analysis; the correct use of useful analytical data increases the efficiency of the organization’s management. And a better solution, in turn, can mean increased operational efficiency, reduced costs, and reduced risk of poor management decisions. Leading organizations are using data analytics to understand company risks and opportunities through big data that can be used in forecasting.
Keywords: Data analysis, big data (Big data), information and analytical technologies, forecasting, management decision making.